2018
DOI: 10.22259/2637-5583.0203001
|View full text |Cite
|
Sign up to set email alerts
|

Cereal Utilization in Nigeria

M.U. Ukwuru,
A. Muritala,
A.O. Iheofor

Abstract: Millet is one of the major cereals utilized in Nigeria to produce kunun zaki, fura and the process involves decortication/dehulling, washing, drying, milling, fermenting, moulding, steaming, and drying. Masa, pito, ogi are all produced from millet. Rice is one of the major cereals in Nigeria which is used to make tuwo and can be consumed with beans soup and masa. It is used to produce kunun by mixing it with millet. The tropical Africa has many cereal crops [5] with diverse utilization most of which are not pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…Lactic acid bacteria are a group of gram-positive, non-respiring, non-spore-forming, non-pigmented, and non-motile cocci or rods that produce lactic acid as the major end product of the fermentation of carbohydrates [7,8]. They are catalase-and oxidase-negative due to a lack of cytochromes and porphyrins.…”
Section: Lactic Acid Bacteria (Lab)mentioning
confidence: 99%
See 3 more Smart Citations
“…Lactic acid bacteria are a group of gram-positive, non-respiring, non-spore-forming, non-pigmented, and non-motile cocci or rods that produce lactic acid as the major end product of the fermentation of carbohydrates [7,8]. They are catalase-and oxidase-negative due to a lack of cytochromes and porphyrins.…”
Section: Lactic Acid Bacteria (Lab)mentioning
confidence: 99%
“…Yeasts are intimately involved in the production of alcoholic beverages due to their ability to ferment sugar into ethanol efficiently and tolerate ethanol concentrations of 15-20% v/v [58]. The genus Saccharomyces, in particular, Saccharomyces cerevisiae is strongly associated with the production of fermented cereal products made for human consumption, especially in alcoholic fermentation [7]. Hammes and others [59] reported that Saccharomyces cerevisiae is the principal yeast of most bread fermentation which causes expansion and leavening of dough, which ultimately give palatability to bread.…”
Section: Yeastmentioning
confidence: 99%
See 2 more Smart Citations
“…they include wheat, rice, maize, sorghum, soya bean, millet, cowpea, ground nut, among others (Ade-Omowaye et. al., 2015;Ukwuru et. al., 2018).…”
Section: Introductionmentioning
confidence: 99%